Incidence of appropriate implantable cardioverter-defibrillator therapy and mortality after implantable cardioverter-defibrillator generator replacement: results from a real-world nationwide cohort. Issue 8 (27th April 2019) - Ruwald, Martin H; Ruwald, Anne-Christine; Johansen, Jens Brock; Gislason, Gunnar; Nielsen, Jens Cosedis; Philbert, Berit; Riahi, Sam; Vinther, Michael; Lindhardt, Tommi B
Abstract: Aims: The safety of omitting implantable cardioverter-defibrillator (ICD) generator replacement in patients with no prior appropriate therapy, comorbid conditions, and advanced age is unclear. The aim was to investigate incidence of appropriate ICD therapy after generator replacement. Methods and results: We identified patients implanted with a primary prevention ICD ( n = 4630) from 2007 to 2016, who subsequently underwent an elective ICD generator replacement ( n = 670) from the Danish Pacemaker and ICD Register. The data were linked to other databases and evaluated the outcomes of appropriate therapy and death. Predictors of ICD therapy were identified using multivariate Cox regression analyses. A total of 670 patients underwent elective ICD generator replacement. Of these, 197 (29.4%) patients had experienced appropriate therapy in their 1st generator period. During follow-up of 2.0 ± 1.6 years, 95 (14.2%) patients experienced appropriate therapy. Predictors of appropriate therapy in 2nd generator period was low initial left ventricular ejection fraction (≤25%) [hazard ratio (HR) 1.87, confidence interval (CI) 1.13–1.95] and appropriate therapy in 1st generator period (HR 3.95, CI 2.57–6.06). For patients with appropriate therapy in 1st generator period, 4-year incidence of appropriate therapy was 50.6% vs. 16.4% in those without ( P < 0.001). Among patients >80 years with no prior appropriate therapy 8.8% of patients experienced appropriate therapy after replacement. Comorbidity burden and advanced age were associated with reduced device utilization after replacement and a high competing risk of death without preceding appropriate therapy. Conclusion: A significant residual risk of appropriate therapy in the 2nd generator was present even among patients with advanced age and with a full prior generator period without any appropriate ICD events.